A preliminary assessment of transition of sst to gst tax regime of SMEs - Ng, Kim-Soon; Ahmad, Abd Rahman; Har, Kar Chun; Hasaballah, Abdel Hafiez Ali (American Scientific Publishers, 2018)
Goods and Service Tax (GST) is disruptive to Small and Medium Enterprises (SMEs) business during the initial stage of its implementation period. However, SMEs are able to manage and adapt to the new tax system through enhancing its human capital and developing of its accounts and information system. This new tax system was implemented in Malaysia on 1st April 2015. It was anticipated to eliminate the inherent weakness of conventional tax system. It was implemented with the purpose of transforming the existing tax structure that will positively impact on the Malaysian economy. As it is a new tax system, it is expected to create uncertainty in the business environment. SMEs are the backbone of the economy of the nation thus, their performance is anticipated to be strongly influenced by GST. The implementation of GST has caused much hullabaloo to various parties. Malaysians have differing views and understandings on the effects of GST implementation. Preliminarily after the first 3 months of its introduction, there are many flaw issues amongst the public and business sectors. Among them are the alleged rising cost of living and unjust taxes. This paper delved to provide a review of existing literature on GST, issues that have arisen and a preliminary assessment of the initial 6 months effects of GST implementation on the Small and Medium Enterprises. Research findings and initial inputs from the periodicals, local news articles, journals, books, interviews, and etcetera were analyzed to provide discussion and recommendation for future research works.